Re-design of Toledo Riverfront - Henriksson, Sara (2014)
Effects of climate change, urbanization and global homogenization are resulted in the degradation of land and losses of natural habitats. Ecological design integrates nature into urban environment by respecting natural ecological principles and processes and creating resilient urban biotopes which also can be used by local urban communities.